Gideon & Otto - Dunrea, Olivier (Green Light readers., 2012)
Otto the toy octopus goes everywhere with Gideon, a small gosling, but while Gideon is playing with some rabbits Otto falls off the wall on which he was left and makes a new acquaintance.